Revisiting state personhood and world politics : identity, personality and the IR subject - Naude, Bianca (New York, NY : Routledge, 2022)
"Breathing fresh air into debates surrounding foreign policy and interstate relations, Bianca Naude presents a holistic theory of states as collectives of people that cannot be reduced to their individual constituents. Moving among current research on the ontological status of the state alongside important arguments in support of the state personhood thesis, Naude begins by exploring Freud's personality theory and the ways in which this theory has evolved over time in response to newer insights from the field of experimental psychology. Recognizing that Freud's work is in many ways outdated, she considers more recent literature on narcissism as an aspect of self-esteem rather than a form of psychopathology, drawing specifically on Kohut's expansion of the concept of narcissism as a normal feature of personality development. Using the South African state as a case study, Naude demonstrates the various ways in which the state presents itself to the outside world on the one hand, and how it wishes to see itself on the other. She further considers how narcissistic defenses help protect the state's ego from criticism and self-judgments. Revisiting State Personhood and World Politics will help readers understand how the state sees itself, why or when the state experiences shame, humiliation, guilt or pride, and how it responds to these self-conscious emotions. It will be a valuable resource to researchers and students of International Relations"--
1. Revisiting state personhood and world politics2. The ontological status of the state3. Personality, identity and the IR subject4. The story of a state person5. Social expectations and personal limitations6. State narcissism and the constraints of reality
Keywords: Political psychology -- South Africa; World politics; Emotions -- Political aspects -- South Africa; South Africa -- Foreign relations; South Africa -- Politics and government; POLITICAL SCIENCE / International Relations / General; PSYCHOLOGY / Personality